2017
DOI: 10.1186/s12917-017-1233-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastric acid-suppressive therapy and biological variation of serum gastrin concentrations in dogs with chronic enteropathies

Abstract: BackgroundSerum gastrin concentration can help diagnose gastrinomas in dogs if >3–10× the upper reference limit (URL), but antisecretory therapy and other conditions can also cause hypergastrinemia. Effects of antisecretory therapy (famotidine or ranitidine, omeprazole) on serum gastrin concentration in dogs with chronic enteropathy (CE) and its biological variation (BV) are unknown. Aim of the study was to evaluate serum gastrin in acid-suppressant-treated or -naïve CE dogs; test the association between serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
1
Order By: Relevance
“…Higher pH inhibits somatostatin release, which increases gastrin release, causing hypergastrinemia [ 52 ]. These findings agreed with these studies [ 53 , 54 ]. Prolonged hypergastrinemia due to chronic PPI use exerts tropic effects in the stomach, which increases the risk of gastric cancer [ 52 ].…”
Section: Discussionsupporting
confidence: 94%
“…Higher pH inhibits somatostatin release, which increases gastrin release, causing hypergastrinemia [ 52 ]. These findings agreed with these studies [ 53 , 54 ]. Prolonged hypergastrinemia due to chronic PPI use exerts tropic effects in the stomach, which increases the risk of gastric cancer [ 52 ].…”
Section: Discussionsupporting
confidence: 94%
“…A study involving 231 dogs with chronic enteropathy receiving antisecretory therapy demonstrated higher levels of serum gastrin in dogs treated with omeprazole. However, serum gastrin levels in these dogs did not exceed 3 times the upper reference limit (URL), excluding the diagnosis of gastrinoma [13]. Notably, the omeprazole group in the present study exhibited mean gastrin levels four times higher than the control group.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies in dogs determined that serum gastric levels were significantly higher in patients treated with PPIs compared to a control group. However, the administration time of the antacids was not standardized [13]. Currently, there have been no long-term studies on the use of PPIs in dogs similar to those conducted in cats.…”
Section: Introductionmentioning
confidence: 99%
“…32 Serum gastrin concentrations may indicate a gastrinoma if increased >10 times above the normal reference interval. 33 Despite the importance of the minimum database comprised of routine clinicopathologic tests, these diagnostic tests usually are not specific for CIE in dogs, and additional biomarkers that are more disease-specific, organ-specific, or both appear to be a very useful additional tool for the management of dogs with CIE.…”
Section: Routine Clinicopathologic Variables In Ciementioning
confidence: 99%